2023
DOI: 10.1038/s41467-023-37505-w
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid magnonics in hybrid perovskite antiferromagnets

Abstract: Hybrid magnonic systems are a newcomer for pursuing coherent information processing owing to their rich quantum engineering functionalities. One prototypical example is hybrid magnonics in antiferromagnets with an easy-plane anisotropy that resembles a quantum-mechanically mixed two-level spin system through the coupling of acoustic and optical magnons. Generally, the coupling between these orthogonal modes is forbidden due to their opposite parity. Here we show that the Dzyaloshinskii–Moriya-Interaction (DMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Spin-dependent electron transport properties can be manipulated by both light and magnetic fields. It is found that HOIPs have a prominent near-infrared circularly polarized light response, which can be used as the detector of circularly polarized light. , Magneto-optical detection showed that the spin-polarized photocurrent of chiral HOIPs could be regulated by the external magnetic field under light illumination . In 2021, Kim et al used HOIPs to produce spin-polarized carriers, making the room-temperature spin light-emitting diode possible .…”
Section: Resultsmentioning
confidence: 99%
“…Spin-dependent electron transport properties can be manipulated by both light and magnetic fields. It is found that HOIPs have a prominent near-infrared circularly polarized light response, which can be used as the detector of circularly polarized light. , Magneto-optical detection showed that the spin-polarized photocurrent of chiral HOIPs could be regulated by the external magnetic field under light illumination . In 2021, Kim et al used HOIPs to produce spin-polarized carriers, making the room-temperature spin light-emitting diode possible .…”
Section: Resultsmentioning
confidence: 99%
“…We have further studied the Dzyaloshinskii–Moriya interaction in layered AFM (CH 3 CH 2 NH 3 ) 2 CuCl 4 through ferromagnetic resonance measurements. 17 This interaction can control the magnetic dynamics particularly in AFM materials, such as collective spin excitations (magnons). The mixed magnon in this AFM material has a simple planar anisotropy.…”
Section: Magnetic Properties Of Different Tmhsmentioning
confidence: 99%
“…1–3). New crystal structures with interesting magnetic properties including spin frustration, 15 magnetic anisotropy, 16 hybrid magnonic, 17 and chiral ferromagnetic 18 were reported.…”
Section: Introductionmentioning
confidence: 99%
“…[28,29] In addition, there is a need to comprehend the design principles for attaining ferromagnetism or antiferromagnetism in HOIPs, as well as the underlying mechanisms contributing to spin alignment, including Dzyaloshinskii-Moriya (D-M) interaction, Jahn-Teller (J-T) distortion, and magnon-magnon coupling. [30,31] The substitution of B 2+ -site ions in ferroelectric HOIPs with magnetic transition metal cations imparts intrinsic multiferroic and magnetoelectric properties; however, their underlying magnetoelectric origin and ferroic coupling mechanism have yet to be verified by experiments.…”
Section: Introductionmentioning
confidence: 99%